Integrated bioinformatic analysis of dysregulated microRNA‐mRNA co‐expression network in ovarian endometriosis - Yong Liu; Linyuan Fan; Lingge Jin; Chang Lu; Ting Li; Zhan Zhang; Chengmao Xie; Shenghui Li; Yudi Zhang; Jian Ren; Dan Lu (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Ovarian endometriosis is a frequently occurring gynecological disease with large socioeconomic impact. Accumulating evidence has suggested that aberrant miRNA‐mRNA interactions are involved in the pathogenesis and progression of ovarian endometriosis. This study aims to identify key miRNAs in ovarian endometriosis by using integrated bioinformatic analysis of a dysregulated miRNA‐mRNA co‐expression network. Material and methods Expression profiling of miRNA and mRNA in three normal endometria and five pairs of ectopic/eutopic endometria from patients with ovarian endometriosis was determined by high‐throughput sequencing techniques. The data were then integrated with the public sequencing datasets (GSE105764 and GSE105765) using a non‐biased approach and a miRNA‐mRNA co‐expression regulatory network was constructed by in‐depth bioinformatic analysis. Results The constructed miRNA‐mRNA network included 87 functionally DEMs, 482 target mRNAs and 1850 paired miRNA‐mRNA regulatory interactions. Specifically, five miRNAs (miR‐141‐3p, miR‐363‐3p, miR‐577, miR‐767‐5p, miR‐96‐5p) were gradually decreased and two miRNAs (miR‐493‐5p, miR‐592) were gradually increased from normal endometria to eutopic endometria, and then ectopic endometria tissues. Importantly, miR‐141‐3p, miR‐363‐3p and miR‐96‐5p belonged to the miR‐200 family, miR‐106a‐363 cluster and miR‐183/96/182 cluster, respectively. Their target mRNAs were mainly associated with cell adhesion, locomotion and binding, which are suggested to play vital regulatory roles in the pathogenesis of ovarian endometriosis. Conclusions Integrated bioinformatic analysis of the miRNA‐mRNA co‐expression network defines the crucial roles of the miR‐200 family, miR‐106a‐363 cluster and miR‐183/96/182 cluster in the pathogenesis of ovarian endometriosis. Further in‐depth functional studies are needed to unveil the molecular mechanisms of these miRNAs, and may provide clues for the optimization of therapeutic strategies for ovarian endometriosis.